2022
DOI: 10.3390/nano12132157
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Aluminum-Matrix Composites Reinforced with AlCoCrFeNi High-Entropy Alloy Nanoparticles by First-Principles Studies on the Properties of Interfaces

Abstract: The present work reports the interfacial behaviors and mechanical properties of AlCoCrFeNi high-entropy alloy (HEA) reinforced aluminum matrix composites (AMCs) based on first-principles calculations. It is found the stability of HEA-reinforced AMCs is strongly dependent on the local chemical compositions in the interfacial regions, i.e., those regions containing more Ni atoms (>25%) or fewer Al atoms (<20%) render more stable interfaces in the HEA-reinforced AMCs. It is calculated that the interfacial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…However, it has been pointed out that Ni was enriched at the edge of the original HEA particle. It has been reported that the electronegativities of Cr, Co, Fe, Ni, and Al atoms are 1.66, 1.88, 1.83, 1.91, and 1.61, respectively, meaning that Ni atoms possessed a better ability to attract electrons from the surrounding Al atoms than those of other metal atoms [ 38 , 39 ]. The charge transfer between Ni and Al atoms was strongest, which promoted Ni to segregate at the layer I/Al matrix interface, thus reducing the total energy of the system.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been pointed out that Ni was enriched at the edge of the original HEA particle. It has been reported that the electronegativities of Cr, Co, Fe, Ni, and Al atoms are 1.66, 1.88, 1.83, 1.91, and 1.61, respectively, meaning that Ni atoms possessed a better ability to attract electrons from the surrounding Al atoms than those of other metal atoms [ 38 , 39 ]. The charge transfer between Ni and Al atoms was strongest, which promoted Ni to segregate at the layer I/Al matrix interface, thus reducing the total energy of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a need for composite materials with high strength characteristics [ 17 , 18 , 19 ]. In some cases, additional requirements are imposed on the composites, including the ability to maintain performance properties at low temperatures (for example, for Arctic/Antarctic regions, deep space, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the experimental study of deformation and fracture under uniaxial tension of composite samples at room and cryogenic temperatures becomes important [ 30 ]. In addition, the combination of various types of components in hybrid metal composite materials is known to provide an increase in physicochemical characteristics [ 9 , 10 , 17 , 18 , 19 , 20 ]. This approach is the most promising for the involved class of nanostructured materials.…”
Section: Introductionmentioning
confidence: 99%